L’E.S.W.T.: Extracorporeal Shock Wave Therapy - Cervera, G.P.; Tammaro, N.; Romano, L.; Toro, G.; Pellegrino, A. (Lo Scalpello - Journal, 2019)
L’E.S.W.T.: EXTRACORPOREAL SHOCK WAVE THERAPY Extracorporeal Shock Wave Therapy (ESWT) is an effective and safe non-invasive therapeutic option for various musculoskeletal pathologies. Extracorporeal shockwave therapy has been widely used in many musculoskeletal problems over the last 25–30 years, for example in case of pseudoarthrosis, plantar fasciitis, lateral epicondylitis, shoulder calcific tendinitis, Achilles tendinopathy, and osteonecrosis of the femoral head. Though the exact effects have not been proven, it has been suggested that shock waves accelerate tissue healing, reduce calcification, and inhibit pain receptors with denervation. As an economic and noninvasive physical therapy with good clinical effects, applications of ESWT have gradually increased in recent years.